Pengembangan media pop-up book terintegrasi augmented reality untuk meningkatkan hasil belajar siswa sekolah dasar - Aminah, Siti; Fakhriyah, Fina; Fajrie, Nur (Papanda Publisher, 2025)
This research is based on the low student learning outcomes in IPAS subjects as well as the lack of innovative and interactive learning media in elementary schools. Therefore, this study aims to develop learning media Pop-Up Book RAYAKU based on Augmented Reality (AR) technology that can improve student learning outcomes. This research is a research and development (R&D) with media development conducted using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were fifth grade students at SDN 4 Sadang and SDN 1 Sadang. Data collection techniques included observation, interviews, questionnaires, tests, and documentation. Data analysis was carried out qualitatively to describe the media development process, and quantitatively to measure the improvement of student learning outcomes. The results of the recapitulation of the validity of learning media from media experts scored 80%, media experts 96%, and teacher practitioners 92%. All three are categorized as “very feasible”. The results of student responses get an average of 90% with the category “very good”. The N Gain test results get an average percentage score of 67.39% categorized as “quite effective”. This shows that ARbased Pop-Up Book RAYAKU learning media is proven to be effective enough to improve student learning outcomes. Thus, this media can be an innovative solution in supporting the implementation of differentiated learning in elementary school